A big Wilms tumor in a 14-months-old boy - Wójtowicz, Agnieszka; Ściślak, Robert; Widłak, Karolina; Nurzyńska-Flak, Joanna (Journal of Education, Health and Sport, 2019)
Introduction. Wilms tumor (nephroblastoma) is a malignant neoplasm located in a kidney. It is typical for children and it occurs almost exclusively in a childhood. Purpose of work, material and methods. The aim of the study is presentation of symptoms, diagnostics and treatment of the massive Wilms tumor in a 14-months-old child. Results. In the paper it was presented the case of 14-months-old boy with the Wilms tumor. The patient did not present typical symptoms of a nephroblastoma, except from a perceptible tumor in a abdomen. US and CT scan confirmed a preliminary diagnosis of the neoplasm. After US, a parasitic cyst was taken into account in a differential diagnostics. Despite a growth the tumor after a pre-operative chemotherapy and a radical nephrectomy was successful. A complete remission was achieved. Discussion. The age of the boy was standard for Wilms tumor. The patient presented the main symptom for nephroblastoma – a large, painless abdominal mass, but without other symptoms (haematuria, malaise and hypertension). A protocol involves a primary treatment with chemotherapy, next surgical resection and later post-operative chemotherapy. The prognosis and survival rate of Wilms tumor depends on pathologic pattern. Relapses are rare in nephroblastoma. Conclusion. The case was not typical form of the Wilms tumor. Doctors should take it into account while diagnosing other illnesses with similar symptoms.